Foreign Investment in Agricultural Land and Legal Protection of Local Farmers (A Comparative Study between Indonesia and Thailand) - Amiludin, Amiludin; Suhadi, Suhadi; Wahanisa, Rofi (Universitas Muhammadiyah Purwokerto, 2026)
This study examines the ownership and control of agricultural land by foreign investors in Indonesia and Thailand, an issue closely related to agrarian sovereignty and the protection of local farmers. The research is motivated by pressures from globalization and economic liberalization, which encourage foreign investment but risk the dominance of capital over agricultural land. The objectives are to analyze the legal framework, mechanisms for farmer protection, regulatory differences between the two countries, and implementation challenges. The research questions focus on how the law regulates foreign land ownership, the legal protection available for farmers, and the key differences between Indonesia and Thailand. This study uses a normative juridical approach with comparative legal analysis, relying on primary, secondary, and tertiary legal sources, and is analyzed qualitatively. Findings indicate that Indonesia restricts foreign ownership through limited rights and domestic legal entities, yet weak enforcement, fragmented oversight, and nominee arrangements allow de facto control by foreign investors. Thailand enforces stricter restrictions, effective corporate oversight, and limited-use rights for farmers, ensuring stronger legal protection. Policy recommendations include comprehensive agrarian law reform, establishment of cross-sector coordinating institutions, strengthened investment supervision, and mandatory application of Free, Prior, and Informed Consent (FPIC) to protect farmers. The study contributes academically to comparative agrarian law research and provides normative guidance for policymakers.